2006
DOI: 10.1055/s-0032-1307930
|View full text |Cite
|
Sign up to set email alerts
|

Selbstständigkeit effizient messen

Abstract: Wer objektiv und standardisiert untersucht, kann Therapieerfolge besser nachweisen als derjenige, der das nicht tut. Deshalb gewinnen objektive Assessments in der Physiotherapie an Bedeutung. physiopraxis startet in Zusammenarbeit mit der AG Assessment der Schweizer Interessengemeinschaft Physiotherapie in der Rehabilitation eine neue Serie über Assessments, die man kennen sollte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It is primarily intended for interdisciplinary rehabilitation teams that use it to plan rehabilitation goals and monitor the success of rehabilitation. It has high reliability, Cronbach's alpha is between 0.96-0.99 when used for neurological patients (Prosiegel et al, 1996;Schädler, 2006). In a study by Jansa et al (2004), it was shown to be a valid and reliable instrument in persons suffering a stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is primarily intended for interdisciplinary rehabilitation teams that use it to plan rehabilitation goals and monitor the success of rehabilitation. It has high reliability, Cronbach's alpha is between 0.96-0.99 when used for neurological patients (Prosiegel et al, 1996;Schädler, 2006). In a study by Jansa et al (2004), it was shown to be a valid and reliable instrument in persons suffering a stroke.…”
Section: Discussionmentioning
confidence: 99%
“…If a person is completely independent, they score a maximum of 64 points. According to Schädler ( 2006 ), the Extended Barthel index is a widely used measure. The instrument is suitable for the acute and rehabilitation phases.…”
Section: Methodsmentioning
confidence: 99%